Pharmacokinetics and relative bioavailability study of two cefquinome sulfate intramammary infusions in cow milk - Li, Shuang; Yu, Na; Tang, Yaoxin; Liu, Chunshuang; Zhang, Ying; Chen, Xiaojie; Wu, Hao; Li, Xiubo; Liu, Yiming (Frontiers in Veterinary Science, 2024)
In this study, two intramammary infusions of cefquinome sulfate were investigated for pharmacokinetics and bioavailability. 12 lactating cows for each group were administered an effective dose of 75 mg/gland for cefquinome, with milk samples collected at various time intervals. The concentrations of cefquinome in milk at different times were determined by the UPLC-MS/MS method. Analyses of noncompartmental pharmacokinetics were conducted on the concentration of cefquinome in milk. Mean pharmacokinetic parameters of group A and group B following intramammary administration were as follows: AUClast 300558.57 ± 25052.78 ng/mL and 266551.3 ± 50654.85 ng/mL, Cmax 51786.35 ± 11948.4 ng/mL and 59763.7 ± 8403.2 ng/mL, T1/2 5.69 ± 0.62 h and 5.25 ± 1.62 h, MRT 7.43 ± 0.79 h and 4.8 ± 0.78 h, respectively. Pharmacokinetic experiments showed that the relative bioavailability of group B was 88.69% that of group A. From our findings, group B (3 g: 75 mg) shows a quicker drug elimination process than group A (8 g: 75 mg), which suggests that the withdrawal period for the new formulation may be shorter.